The Effect of Independent Commissioners and Capital Intensity on Tax Planning - Serena, Rinasda; Nuswantara, Dian Anita (PT Aksara Indo Rajawali, 2024)
This study aimed to examine the effect of independent commissioners and capital intensity on tax planning by manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange 2020-2023. This study has a sample of 40 consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange (IDX) with predetermined criteria during the 2020-2023 period. The independent variables of this study are independent commissioners and capital intensity. The dependent variable in this study is tax planning, which is measured using ETR. This study uses secondary data from the company's financial statement and annual report. The analysis used in this study is panel data regression with the EViews-12 program. Partially, the results show that independent commissioners and capital intensity do not affect tax planning.